PRO KONTRA PROSES PENGESAHAN UU NO. 16 TAHUN 2017, SERTA IMPLEMENTASI DAN IMPLIKASINYA TERHADAP ORGANISASI MASYARAKAT - Fadli Afriandi; Fachriza Ariyadi (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2021)
This paper looks at how a public policy process is issued, implemented, and its implications. The policy issued was the stipulation of Law no. 16 of 2017 (Law on community organizations) in lieu of Perppu No. 2 of 2017 (Perppu for community organizations). The main thesis proposed in this paper is that the policy of passing the law on community organizations is an attempt by the state to protect the Pancasila ideology, which is the sole ideology in Indonesia. This paper is prepared using qualitative methods by collecting data through Library Research. The findings of this study are that the issuance of the first law on community organizations cannot be separated from debates in parliament. The parties in parliament are inconsistent with their party ideology. Supporting or rejecting the law on community organizations is based on the pragmatic interests of the party. Secondly, the existence of the Community Organization Law makes it difficult for community organizations to stand and makes it easier for the government to dissolve community organizations that are not under Indonesian ideology. Third, the first community organization that was dissolved after the law on community organizations took effect was the Islamic Defenders Front (FPI).